2018
DOI: 10.1590/1807-1929/agriambi.v22n8p519-524
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous salinity in the root system of bell pepper in greenhouse

Abstract: A B S T R A C TThe split-root technique was used as a strategy to reduce saline stress on pepper. A completely randomized design with six treatments and four replicates was used. The treatments consisted of six saline water application strategies (T1 -salinized nutrient solution (S1 = 1.4 dS m ) throughout the cycle, T3 -S1 and S2 throughout the cycle, using two emitters and without splitting the root system, T4 -S1 and S2, using two emitters and splitting the root system by a plastic film, T5 -S1 and S2, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, these adaptive strategies are inefficient to cope with the osmotic and ionic effects, which induce a reduction in chloroplast pigments and in the photosynthesis, growth and production of crops (Yang et al, 2020). Oliveira et al (2018) found that irrigation with 4.5 dS m-1 saline water reduces growth and production in bell pepper. The authors stated that the highest fruit yields were achieved with the use of low-salinity water, a mixture of non-saline and saline waters and fortnightly alternation of high-salinity water.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these adaptive strategies are inefficient to cope with the osmotic and ionic effects, which induce a reduction in chloroplast pigments and in the photosynthesis, growth and production of crops (Yang et al, 2020). Oliveira et al (2018) found that irrigation with 4.5 dS m-1 saline water reduces growth and production in bell pepper. The authors stated that the highest fruit yields were achieved with the use of low-salinity water, a mixture of non-saline and saline waters and fortnightly alternation of high-salinity water.…”
Section: Introductionmentioning
confidence: 99%
“…Low water loss in seedlings under 50% and 70% of shading favored the elongation of the root system and its exploitation in the soil (Oliveira et al, 2018), the moisture was longer kept, due to lower evaporation substrate, which favored its development, in the seedlings with smaller XL. However, it should be noted that even with smaller roots under 0% and 30% of shading levels, there was an increase in the morphometric aspects of reserve structures, which contributes to their ecological tolerance to environmental conditions.…”
Section: -9mentioning
confidence: 99%
“…This condition is worse in regions with low precipitation, irrigation with low-quality water, successive application of fertilizers and amendments with high salt content (Silva et al, 2020). The soil salinity effects on plants are usually related to the dynamics of water and nutrient absorption by roots and the toxic levels of some elements (Maciel et al, 2012;Oliveira et al, 2018;Sá et al, 2019). Beloti et al (2022) Bell pepper germination and seedling's...…”
Section: Introductionmentioning
confidence: 99%